Varicose veins: a clinical profile - Agarwal, Pooja; Reza, Ali; Desai, Darshana; Vardey, Mohit (International Surgery Journal, 2021)
Background: The CEAP classification includes classifying varicose veins on the basis of their clinical, etiological, anatomical and pathophysiological classification. Methods: It was a prospective study of 50 patients presenting to a tertiary care hospital, MGM Medical College and Hospital, Kamothe, Maharashtra with varicose veins over a period of 2 years (November 2019 to November 2021). Institute Ethics Committee approval was obtained before start of study. All patients clinically diagnosed of symptomatic or complicated primary lower limb varicose veins with saphenofemoral and/or sapheno-popliteal incompetence with or without perforator incompetence were included. All cases with recurrent varicose veins were excluded. Result was tabulated and analysed at the end of the study using IBM SPSS software. Results: The age group with maximum varicose vein was between 21-30 years and incidence being more common in male population. The majority of the patients had massive varicose veins (C2). Pain was the most frequent presenting symptom. The majority of the study group had both saphenofemoral junction and perforator incompetence. Primary varicose veins are far more common (76%) than secondary and congenital varicose veins. Conclusions: Varicose veins are highly common in the Indian population. The CEAP classification has been a major contributor to advances in the field of varicose veins since its inception, and it has now become universally accepted due to its simplicity and reliability.